2017
DOI: 10.1002/lol2.10047
|View full text |Cite
|
Sign up to set email alerts
|

Can small zooplankton mix lakes?

Abstract: The idea that living organisms may contribute to turbulence and mixing in lakes and oceans (biomixing) dates to the 1960s, but has attracted increasing attention in recent years. Recent modeling and experimental studies suggest that marine organisms can enhance turbulence as much as winds and tides in oceans, with an impact on mixing. However, other studies show opposite and contradictory results, precluding definitive conclusions regarding the potential importance of biomixing. For lakes, only models and lab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This implies that the products L w of the eddy sizes L and velocities w , generated by aquatic organisms, need to overcome those geophysical diffusivities (Kunze et al 2006). From all known observations so far, it appears that biogenic turbulence does not significantly contribute to mixing or stratification changes (Katija 2012, Wang & Ardekani 2015, Simoncelli et al 2017. Although Noss & Lorke (2012) showed that swimming zooplankton can significantly enhance TKE dissipation in direct proximity by creating eddies in their wakes and by dragging water along, the generated L are too short to have a macroscopic effect.…”
Section: Bioconvection In Lakesmentioning
confidence: 99%
“…This implies that the products L w of the eddy sizes L and velocities w , generated by aquatic organisms, need to overcome those geophysical diffusivities (Kunze et al 2006). From all known observations so far, it appears that biogenic turbulence does not significantly contribute to mixing or stratification changes (Katija 2012, Wang & Ardekani 2015, Simoncelli et al 2017. Although Noss & Lorke (2012) showed that swimming zooplankton can significantly enhance TKE dissipation in direct proximity by creating eddies in their wakes and by dragging water along, the generated L are too short to have a macroscopic effect.…”
Section: Bioconvection In Lakesmentioning
confidence: 99%
“…2003;Rinke et al 2007). However, it is not certain how C DVM increases with respect to C b in other lakes, because its value depends on the presence of other migrating species, predators and light conditions (Ringelberg 2010;Simoncelli et al 2017). The experiment by Houghton et al (2018) showed that A. salina ( l O = 5-8 mm), swimming in tank-averaged concentration C b > 46 org.…”
Section: Mixingmentioning
confidence: 99%
“…2). However, the result may depend on the organisms' concentration and how the migration was triggered in artificial laboratory conditions (Simoncelli et al 2017). Experimental measurements in a stratified tank by Houghton et al (2018) indicate instead that collective motions, arising from small zooplankton swimming at high concentration, can trigger fluid instabilities bigger than the size of the individual organism and lead to irreversible mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In freshwater ecosystems the so-called pusher swimmers 20,21 like the freshwater D. magna individuals, produce mean dissipation rates from 0.034 to 0.018 cm 2 s −3 , which are associated to viscous trail dissipation 22 , although when forming schools Daphnia might produce maximum dissipations of ε = 2.8 cm 2 s −3 21 . Therefore, like many zooplankton species, D. magna might potentially be important for vertical mixing in weak mixing ambient flows 21,23 . In contrast, in aquatic ecosystems, turbulence plays an additional role as a stressor by modifying the swimming capacity and survival of organisms 4 , to shifting community structure 24 or producing active cyclomorphosis 25 .…”
Section: Introductionmentioning
confidence: 99%